Research of the effect of non-transitional raw materials on the rheological indicators of the semi-finished products of formed potato chips - Kovtun, Alina; Kovbasa, Vladimir; Pichkur, Vitaliy (My University, 2019)
The paper considers the current state and prospects of enrichment of formed potato chips with bran, pulp and cryopowder containing from 14 to 40% of food fibers. The importance of the use of food fibers, which is connected with the prevention of alimentary-dependent diseases, has been substantiated. The optimum size of the degree of grinding of rye bran, barley bran, pumpkin seeds pulp, broccoli cryopowder and red beetroot cryopowder and their influence on rheological parameters of semi-finished products have been determined. The influence of temperature and time on change of maximum viscosity of model solutions of potato semi-finished potato products has been investigated. В статті розглянуто сучасний стан і перспективи збагачення формованих картопляних чіпсів висівками, жмихом та кріопорошками які містять у своєму складі 14 – 40 % харчових волокон. Обгрунтовано важливість використання харчових волокон, що пов’язано з профілактикою аліментарно-залежних захворювань. Визначено оптимальні розміри ступеня подрібнення ВЖ, ВЯ, ЖГН, КБ та КЧБ та їх вплив на реологічні показники напівфабрикатів. Досліджено вплив температури та часу на зміну максимальної в’язкості модельних розчинів картопляних напівфабрикатів.
Keywords: chips; food fiber; semi-finished products; чіпси; харчові волокна; напівфабрикати; кафедра готельно-ресторанної справи; кафедра технології хлібопекарських і кондитерських виробів